Coriander Seeds in Diet - Tabassum Khan Nida (Journal of Advances in Plant Biology, 2019)
Coriander, commonly known as Sabit dhania in Pakistan is a well-known spice used in traditional cooking. It is an essential component of ayurvedic medicine used for the treatment of digestion and gastric ailments. Coriander seeds are available throughout the year as whole seeds and in powdered form. Fresh Coriander seeds possess earthy bitter flavour with strong aroma. Essential oils of its seed extracts possess numerous valuable constituents which could be exploited for the preparation of medicinal combatants against several acute and chronic diseases.
Keywords: Apiaceae